DYNAMICS OF PLANTATIONS IN NORTH SUMATRA FROM THE COLONIAL TO POST-COLONIAL ERA: DINAMIKA PERKEBUNAN DI SUMATERA UTARA ERA KOLONIAL HINGGA PASCA KOLONAL - Yusra Dewi Siregar; Fitri Khoirun Nisa; Junelma Hamdani Ginting; Muhammad Zahran Yassar Napitupulu; Nurul Fadhilah; Sutan Raja Hendi Fiirmansyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
North Sumatra is the best producing region for tobacco leaves which has a high reputation in plantations and has an influence on the economy of the city of Medan, North Sumatra. This research uses qualitative research methods with data collection techniques through literature study. Researchers also use steps in historical research such as (1) topic selection, (2) heuristics or source collection, (3) source verification or criticism, (4) interpretation and (5) historiography or historical writing. The research results show that the North Sumatra region is one of the regions that has an important position in the history of plantations in Indonesia from the colonial to post-colonial period.